Development of learning materials based on FlipBook contents to support blended learning learning process at IKIP Budi Utomo Malang - Agusti Mardikaningsih; Praharisti Kurniasari (Universitas Sarjanawiyata Tamansiswa, 2018)
The purpose of this study was to find out the process of developing steps and to know the feasibility and validity of flip book-based teaching materials in the design and learning strategies at Budi Utomo IKIP. This development research uses the ADDIE Model. The ADDIE model is a general learning system model and is one of the models in product development, the application of the ADDIE model in learning design facilitates a learning environment adapted to existing problems. Each stage in the ADDIE model has an evaluation so that each stage will affect the next stage. The results of the study show that overall the interactions that occur in the blended learning process using flip book teaching materials are quite satisfying. This means that there is a significant process of interaction between teachers and students. Based on the trials that have been done to material experts, media experts and students, it can be concluded that flip-book teaching materials support blended learning with each percentage of (1) material experts (96.2%) with valid/feasible criteria , (2) Media experts (95%) with valid / feasible criteria, (3) Individual students (97.5%) with valid / feasible criteria, (4) Small group students (94.5%) with valid / feasible criteria , (5) Large group students (93%) with valid / feasible criteria. Student learning outcomes have also shown mastery learning (80.9%). This shows that flip-book teaching material as a support for blended learning is successful in providing a positive effect on student learning outcomes.